Orientação para a aprendizagem, gestão por competências e comprometimento organizacional nas instituições de ensino superior - Zamberlan, Carlos Otávio (2006)
Society is in a transitional period between knowledge and industrial areas where the last is one of the most important resources for the nations. So, the major teaching institutions (MTIs) have a prevalent role in the new economical scenery due to professional s formation that will act in economy (economics). This work has the objective of verifying differences in the guidance for learning, competences and organizational compromising of the MTIs supervisors of Santa Maria-RS because it is important that the professional of the educational area be in a continuous learning, developing their competences in order to give a higher quality to teaching programs (plans), research and extension developed in the university and they should be supported and encouraged by their leaders. A questionary was applied to the coordinators of graduation courses. This questionary observed all the study constructors and tried to characterize, in a descriptive way, the supervisors of these courses in their respectives MITs. The data analysis was done through a descriptive statistic and U test, a non-parametric test. It was found out that MTIs of Santa Maria-RS are oriented to the organizational learning and for competences, besides the supervisors of graduation courses of these MTIs are engaged in calculating, normative and affectionate manner. However, the MTIs show meaningful differences in some studies variables. The differences may be explained through the way the professor enters.